First morphometric and molecular characterization of Fasciola spp. in Northwest Tunisia - Hammami, Inés; Ciuca, Lavina; Paola Maurelli, Maria; Romdhane, Rihab; Sassi, Limam; Ridha Rjeibi, Mohamed; Farhat, Nadia; Kouam Simo, Alain; Rinaldi, Laura; Rekik, Mourad; Gharbi, Mohamed (Springer, 2023)
The aim of this study was to characterize the Tunisian Fasciola spp. flukes by morphometric and molecular analyses. Flukes were collected from livers of sheep slaughtered in Sejnane slaughterhouses (Bizerte gouvernorate, Northwest Tunisia) between January and March 2021.